Analisis kesesuaian materi fisika untuk diintegrasikan dengan materi tsunami pada buku teks pelajaran fisika SMA/MA - amira tiara wulandari; Ahmad Fauzi; Yenni Darvina; Syafriani Syafriani (Universitas Negeri Padang, 2019)
Indonesia is a country that often experiences natural disasters. Disaster mitigation efforts that must be done is to add knowledge and understanding of disasters through education. Appropriate subjects to be integrated with disaster material are Physics subjects. Physics learning integrated with Tsunami material is well suited to be applied in Indonesia, especially in the West Sumatra region. The implementation of the 2013 curriculum depends on the implementation of the Content Standards which provide a gap to integrate Physics material with the Tsunami material and the Standards for Facilities and Infrastructure, namely textbooks. There is a need to develop textbooks that are integrated with Tsunami material. But before integrating Tsunami material with Physics material, there needs to be an analysis to see the Physics material that is suitable to be integrated with Tsunami material. This study aims to determine the level of compatibility of Physics material in high school / MA class X physics textbooks with Tsunami material. This type of research is a descriptive study. The population in this study were all textbooks for Class X High School Physics Physics published in Indonesia. The sample in this study was the 2016 revised edition of the X grade high school physics textbook published by Erlangga. The data in this study were taken using assessment instruments and data collection techniques through documentation studies.The findings of this study indicate that the level of compatibility of Physics material with Tsunami material in Physics textbooks for SMA / MA class X semester 1 for KD 3.1 is not suitable (27%), KD 3.2 is not suitable (27%), KD 3.3 is suitable kurag (33%) , KD 3.4 is quite suitable (53%), KD 3.5 is not suitable (20%) and KD 3.6 is not appropriate (20%). The level of suitability of Physics material with Tsunami material in the Physics textbook of SMA / MA class X semester 2 for KD 3.7 is quite appropriate (47%), KD 3.8 is less appropriate (27%), KD 3.9 is quite appropriate (47%), KD 3.10 is quite appropriate (60%), and KD 3.11 are not appropriate (20%).